Microcontrolled and networked based mobile robot electronic system - Castro, Filipe Campos Meira (2016)
Robotics is increasingly on the agenda to perform both complex tasks in uninviting environment and also for routine actions of our day-to-day. The challenges and demands are constant. The back-office work is demanding, highly skilled and requires a lot of dedication, research and tenacity. Clearly and concisely, this work illustrates the foundations for a machine, the steps to get there, a prospect of easy and reliable use. Enjoy this auspicious and inspiring reading.